Victory party for defeat of Proposition 102. - Sahl, Ted (photographer):::Creator::::::::::::
Victory party after the defeat of California Proposition 102: (left-to-right) unidentified man, Ken Yeager and Paul Wysocki cutting a cake that reads "Thank you Volunteers.